Sustainable Water Resource from fractured Metasedimentary Rocks in West Coast of Peninsular Malaysia - Sapari, Nasiman (2010)
Groundwater in fractured metasedimentary rock in Malaysia is a potential source of water for drinking and industrial uses. Industries including agricultural processing, mineral water bottling, manufacturing and golf courses are pumping the water from the underlying fractured rocks. Fifty eight tubewells belong to private companies operating in various places in the West Coast of Peninsular Malaysia were evaluated for their yield and quality of water. Rotary air-percussion methods were used for the drilling to a maximum depth of 200 m. The productivity of the wells and the characteristics of the aquifer were evaluated by pumping test using both the constant discharge rate and steps drawdown methods. The average yield of the wells at allowable drawdown of 40 m was found to be 416 m3 per day. Results from water quality analysis indicate that the water is fresh with an average total dissolved solids (TDS) concentration of 101 to 150 mg/L. The hardness of the water varies from as low as 13 mg/L to a maximum of 353 mg /L. On the average, the water is moderately hard with the average hardness value of 80 mg/L. The water facies of the groundwater was found to be of calcium-sodium-bicarbonate water.